Construction of a tree from a given single order traversal and also find the other order traversal of a tree - Sharma, Vaibhav (International Journal of Computer Sciences and Engineering, 2025)
As we know that tree traversal means to visit every node of a tree exactly once [1]. We can traverse a tree in three way these are Inorder, Preorder and Postorder. We can easily construct a tree from given two order these order can be Inorder and Preorder, Inorder and Postorder etc. Here we will be construct the tree from given one order and after constructing the tree we will find the other order traversal of a tree